Heat Engineering and Economical Justification of Selection of Optimum Air Heating Temperature in Recuperators of Heating Continuous Furnaces at Machine-Building Enterprises - V. I. Timoshpolsky; I. A. Trusova; D. V. Mendelev; M. L. German (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a methodology for calculation of recuperative heat exchangers applied at heating continuous furnaces of press-forging production at machine-building enterprises. Technical and economic calculations of an optimum air heating temperature have been made taking needle-shape heat exchangers in the RUE MAZ heating continuous  furnaces as an example while varying furnace capacity, cost of power carriers and heat-exchange devices.